Preparation method of binder for forming carbon adsorbent
By mixing lignin sulfonate with natural rubber and combining with carbon powder to form a composite modified binder, the problem of poor strength maintenance and insufficient bonding in a high humidity environment during the molding of existing carbon adsorbents is solved, and a carbon adsorbent with high strength, water resistance and high adsorption properties is achieved.
Patent Information
- Application Number
- CN202411774279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-28
AI Technical Summary
The binder used in the molding process of existing carbon adsorbents has poor strength maintenance in high humidity environments and insufficient bonding with carbon powder, making it difficult to meet the needs of large-scale production.
Lignosulfonate is mixed in proportion with natural rubber, and a viscous emulsion is formed by heating and stirring, and then a composite modified binder powder is obtained by drying. Then it is mixed with the carbon powder at a mass ratio of 10:90, deionized water is added, and pressed by stirring and hydraulic molding machine to form a high-strength carbon adsorbent.
It significantly improves the adhesion, water resistance and bonding with carbon powder of lignin sulfonate, enhances the stability and adsorption properties of carbon adsorbents, and is suitable for large-scale production and maintains good performance in high-humidity environments.
Smart Images

Figure CN119701906A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of binders, and in particular relates to a method for preparing a binder for forming a carbon adsorbent. Background Art
[0002] As environmental pollution becomes increasingly serious, carbon adsorbents are increasingly being used in water treatment, air purification, and waste gas treatment. Carbon adsorbents adsorb harmful substances from water or air, such as organic pollutants, heavy metal ions, and gases, making them an efficient and cost-effective treatment method. However, improvements in the carbon adsorbent's preparation process and physical and chemical properties, particularly the binder used in the molding process, directly impact its adsorption performance, mechanical strength, and durability.
[0003] Traditional carbon adsorbents typically rely on natural or chemically synthesized adhesives during their preparation. While natural adhesives like starch and gelatin are widely available and environmentally friendly, they lack adhesion and water solubility, often failing to meet the requirements for high strength and water resistance. While chemically synthesized adhesives like polyacrylic acid and polyvinyl alcohol offer significant strength enhancement, they suffer from limited adsorption performance. Furthermore, some chemical adhesives may release harmful substances or cause secondary environmental pollution over time.
[0004] Lignin, an important natural polymer, is widely present in the cell walls of plants. Lignin has excellent adsorption properties in water treatment and has become a focus of researchers due to its wide availability, low price, and environmental and non-toxic nature. However, lignin has poor solubility, making it difficult to use directly as a binder. To overcome this problem, scientists have improved the solubility, adhesion, and water resistance of lignin through chemical modification methods such as sulfonation and esterification, thus providing new possibilities for the application of lignin in carbon adsorbents.
[0005] In recent years, lignin sulfonates, as a new, environmentally friendly binder, have shown great potential in the preparation of carbon adsorbents. Through sulfonation, lignin's hydrophilicity and solubility are significantly enhanced, improving its dispersibility in aqueous solvents and making it an ideal binder. Furthermore, lignin sulfonates not only possess excellent adhesive properties, but their strength and water resistance can also be further improved by adjusting the degree of sulfonation and adding modifiers, thereby effectively enhancing the stability and adsorption performance of carbon adsorbents.
[0006] Despite the numerous advantages of lignin sulfonates as binders, their application in carbon adsorbent molding still faces challenges, such as maintaining strength in high-humidity environments and poor bonding with carbon powder. Therefore, developing a modification method that enhances the bonding properties and water resistance of lignin sulfonates has become a key research focus. Improving the hydrophilicity and bonding properties of lignin sulfonates, as well as improving their stability in humid environments, to make them more suitable for large-scale carbon adsorbent production, is a pressing technical challenge.
[0007] To this end, we provide a method for preparing a binder for carbon adsorbent molding that can improve the adhesion, water resistance and binding properties of lignin sulfonate with carbon powder. Summary of the Invention
[0008] The object of the present invention is to overcome the deficiencies in the prior art and to provide a method for preparing a binder for forming a carbon adsorbent.
[0009] The object of the present invention is achieved as follows: A method for preparing a binder for forming a carbon adsorbent, comprising the steps of
[0010] S1: Lignin sulfonation reaction: including lignin sulfonation reaction with sulfonic acid to obtain lignin sulfonate;
[0011] S2: Composite modification treatment: lignin sulfonate and natural rubber are mixed in proportion, and the lignin sulfonate and natural rubber are dissolved in deionized water; the mixture is heated and stirred until a viscous emulsion is formed; and the water in the solution is removed by drying to obtain a composite modified binder powder;
[0012] S3: Molding of carbon adsorbent: Mix the composite modified binder and carbon powder in a mass ratio of 10:90; add deionized water with a mass ratio of water to carbon powder of 1:1.5 to ensure uniform mixing, and stir for 15-20 minutes to ensure that the various components are completely and evenly mixed, so that the composite modified binder and carbon powder are fully mixed to form a mixture; transfer the mixture to a molding mold and use a hydraulic molding machine to press it with the pressure set to 300MPa for 30 seconds to ensure the density and strength of the carbon adsorbent.
[0013] Furthermore, the step S1 includes:
[0014] S11: mixing lignin and sulfonic acid in a mass ratio of 1:4 and adding the mixture into a reactor;
[0015] S12: heating the reaction vessel to 150-160° C. and stirring the reaction vessel until the sulfonic acid and lignin are fully reacted to produce lignin sulfonate;
[0016] S13: After the reaction is completed, the mixture is cooled to room temperature, deionized water is added for dilution, and the mixture is stirred to form a lignin sulfonate solution;
[0017] S14: removing excess sulfonic acid and concentrating the lignin sulfonate to a solid form.
[0018] Furthermore, the step S2 includes:
[0019] S21: mixing lignin sulfonate and natural rubber in a mass ratio of 9:1;
[0020] S22: dissolving the lignin sulfonate solid and natural rubber in deionized water, with the amount of water being 5 times that of the lignin sulfonate;
[0021] S23: heating to 60°C and stirring to ensure that the lignin sulfonate and the natural rubber are completely mixed;
[0022] S24: further heating; continuing to heat the solution to 80° C. and stirring until a viscous emulsion is formed;
[0023] S25: removing water from the solution by spray drying or vacuum drying to obtain a composite modified binder powder.
[0024] The step S3 further includes: pre-drying the formed carbon adsorbent at 60° C. to reduce the moisture content to below 10%; and further drying the carbon adsorbent at a temperature maintained at 60° C. to reduce the moisture content to below 5%.
[0025] Furthermore, step S1 further includes adding hydrogen chloride gas as a catalyst during the sulfonation reaction to promote the activation of sulfonic acid. The amount of hydrogen chloride added is 0.5% of the lignin mass, which can improve the sulfonation efficiency and increase the solubility of lignin sulfonate.
[0026] Furthermore, the step S1 further includes dimethylsulfonamide (DMSO) as a solvent. DMSO can effectively improve the solubility of lignin and the rate of sulfonation reaction, and the added amount is controlled within 5% of the lignin quality.
[0027] Furthermore, after obtaining the lignin sulfonate solution, polyvinyl alcohol (PVA) or polyacrylic acid (PAA) is added as a modifier in an amount of 3-5% of the lignin sulfonate. The solution is heated to 60°C and continuously stirred until the modifier is completely dissolved and evenly distributed. This can significantly improve the adhesion and water resistance of the lignin sulfonate, allowing it to maintain good strength in high-humidity environments. At this point, the lignin sulfonate solution already contains the modifier, and subsequent concentration, drying, and other steps are consistent with the above method.
[0028] Furthermore, through nitric oxide (NO x) or ozone treatment of the lignin sulfonate surface to achieve oxidative modification of the lignin sulfonate, further improving its hydrophilicity and activity, thereby enhancing its binding to carbon powder. The oxidation treatment time is controlled to be 30-60 minutes, and the oxidant concentration is 10%.
[0029] Beneficial effect: This technical solution optimizes the preparation method of lignin sulfonate as a binder and uses nitrogen oxide (NO x ) or ozone treatment effectively improves its hydrophilicity, activity and binding properties with carbon powder; and improves the formability and stability of the carbon adsorbent; improves the adsorption performance, especially the effect in a water-based environment; improves moisture resistance and hydrolysis resistance, and enhances the durability of the product; enhances the environmental protection and sustainability of the product; reduces production costs, improves economic benefits and market competitiveness; and enhances the adjustability of the adsorbent performance to meet different needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Flowchart of the invention. DETAILED DESCRIPTION
[0031] Example 1, as Figure 1 As shown, the purpose of the present invention is achieved as follows: a method for preparing a binder for carbon adsorbent molding, comprising the steps of
[0032] S1: Lignin sulfonation reaction: including lignin sulfonation reaction with sulfonic acid to obtain lignin sulfonate;
[0033] Step S1 includes: S11: mixing lignin and sulfonic acid in a mass ratio of 1:4, and adding the mixture into a reactor;
[0034] S12: heating the reaction vessel to 150-160° C. and stirring the reaction vessel until the sulfonic acid and lignin are fully reacted to produce lignin sulfonate;
[0035] S13: After the reaction is completed, the mixture is cooled to room temperature, deionized water is added for dilution, and the mixture is stirred to form a lignin sulfonate solution;
[0036] S14: removing excess sulfonic acid and concentrating the lignin sulfonate to a solid form.
[0037] S2: Composite modification treatment: lignin sulfonate and natural rubber are mixed in proportion, and the lignin sulfonate and natural rubber are dissolved in deionized water; the mixture is heated and stirred until a viscous emulsion is formed; and the water in the solution is removed by drying to obtain a composite modified binder powder;
[0038] Step S2 includes: S21: mixing lignin sulfonate and natural rubber in a mass ratio of 9:1;
[0039] S22: dissolving the lignin sulfonate solid and natural rubber in deionized water, with the amount of water being 5 times that of the lignin sulfonate;
[0040] S23: heating to 60°C and stirring to ensure that the lignin sulfonate and the natural rubber are completely mixed;
[0041] S24: further heating; continuing to heat the solution to 80° C. and stirring until a viscous emulsion is formed;
[0042] S25: removing water from the solution by spray drying or vacuum drying to obtain a composite modified binder powder.
[0043] S3: Molding of carbon adsorbent: Mix the composite modified binder and carbon powder in a mass ratio of 10:90; add deionized water with a mass ratio of water to carbon powder of 1:1.5 to ensure uniform mixing, and stir for 15-20 minutes to ensure that the various components are completely and evenly mixed, so that the composite modified binder and carbon powder are fully mixed to form a mixture; transfer the mixture to a molding mold and use a hydraulic molding machine to press it with the pressure set to 300MPa for 30 seconds to ensure the density and strength of the carbon adsorbent.
[0044] Step S3 also includes: pre-drying the formed carbon adsorbent at 60° C. to reduce the moisture content to below 10%; and further drying the carbon adsorbent at 60° C. to reduce the moisture content to below 5%.
[0045] Example 2:
[0046] Selection and pretreatment of lignin raw materials: Lignin selection: Lignin from agricultural waste (such as straw, sawdust, bamboo) is selected as raw material, with the moisture content controlled at 10-15% and the purity requirement being above 85%; selecting small molecular lignin particles helps improve reaction efficiency.
[0047] Lignin pretreatment: Mechanically crush the lignin particles until they reach a 40-mesh screen to ensure uniformity and sufficient reaction. Pre-dry at 60°C to reduce the moisture content to below 10%, which helps improve the efficiency of the sulfonation reaction. Use a 1:4 mass ratio of sulfonic acid to lignin. Use 98% industrial sulfonic acid. If using a sulfonic acid solution, choose a 20-25% concentration to ensure adequate sulfonation. Use an autoclave with good temperature control to ensure stable reaction temperature and pressure. Using an autoclave enhances the contact efficiency between the sulfonic acid and lignin and reduces reaction time. The reaction temperature is set at 150-160°C. Excessively high temperatures can easily lead to lignin degradation, while excessively low temperatures can result in incomplete reaction. Maintain a temperature of 155°C ± 5°C. A high-speed stirrer is used during the lignin sulfonation reaction, maintaining a stirring rate of 300-500 rpm to ensure thorough mixing of the reactants and avoid local overheating.
[0048] Example 3:
[0049] Step S1 also includes adding hydrogen chloride gas as a catalyst during the sulfonation reaction to promote the activation of sulfonic acid. The amount of hydrogen chloride added is 0.5% of the lignin mass, which improves the sulfonation efficiency and increases the solubility of lignin sulfonate.
[0050] Example 4:
[0051] Step S1 further includes dimethylsulfonamide (DMSO) as a solvent. DMSO can effectively improve the solubility of lignin and the rate of sulfonation reaction. The added amount is controlled within 5% of the lignin mass.
[0052] Lignin was dissolved in DMSO, ethanol and water respectively, and the solubility of lignin in each solvent (g / L) was measured. Comparison of experimental data:
[0053] Solubility is determined spectrophotometrically or gravimetrically.
[0054]
[0055] Analysis: The solubility of lignin in DMSO is significantly higher than that in other solvents, reaching 6.8 g / L, which is 223.8% higher than that in water solvent (2.1 g / L). This shows that DMSO can significantly improve the solubility of lignin.
[0056] The polarity and good solubility of DMSO enable it to effectively break the hydrogen bonds between lignin molecules, thereby greatly improving the solubility of lignin in the solvent.
[0057] Sulfonation reaction rate test
[0058] Sulfonation reactions were carried out in DMSO, ethanol, and water, and the degree of sulfonation was measured at different time points to calculate the reaction rate. The degree of sulfonation can be measured by elemental analysis (determination of hydrogen, carbon, and sulfur content).
[0059]
[0060] Reaction rate constant calculation:
[0061] Assuming that the sulfonation reaction follows first-order kinetics, the reaction rate constant (k) can be calculated using the following formula:
[0062]
[0063] Where C0 is the concentration at the start of the reaction, and Ct is the concentration at time t.
[0064] The reaction rate constant (k) was obtained by fitting the data.
[0065]
[0066] Analysis: In DMSO solvent, the sulfonation reaction rate constant of lignin is 0.92h-1, which is 109.1% higher than that of water solvent (0.44h-1).
[0067] The increase in the reaction rate constant indicates that DMSO can significantly accelerate the sulfonation reaction, which may be because DMSO can not only effectively dissolve lignin, but also promote the introduction of sulfonic acid groups by forming complexes with lignin molecules.
[0068] According to experimental data, dimethylsulfamide (DMSO) as a solvent significantly improves the solubility of lignin and the rate of sulfonation reaction: Solubility: The solubility of lignin in DMSO reaches 6.8g / L, which is 223.8% higher than that of water solvent (2.1g / L), indicating that DMSO has obvious advantages in improving the solubility of lignin. Reaction rate: In DMSO, the sulfonation reaction rate constant of lignin is 0.92h-1, which is 109.1% higher than that of water solvent, indicating that DMSO can significantly accelerate the sulfonation reaction process. Therefore, DMSO as a solvent has a significant promoting effect in the sulfonation reaction of lignin, can effectively improve the solubility of lignin and the rate of sulfonation reaction, and provides important support for the optimization of the lignin sulfonation process.
[0069] Example 5:
[0070] After the reaction is completed, the heating system is immediately turned off, the reaction solution is cooled to room temperature, and the unreacted sulfonic acid and by-products are removed by centrifugation. After separation, the supernatant is collected to obtain a lignin sulfonate solution.
[0071] The obtained lignin sulfonate solution is fully washed with deionized water to remove excess sulfonic acid until the pH value of the washing liquid is close to 7, ensuring the purity and environmental friendliness of the product.
[0072] The washed solution is concentrated to remove water until a lignin sulfonate solution of appropriate concentration (concentration range 30-50%) is obtained.
[0073] The concentrated solution is dried to obtain lignin sulfonate powder. The drying temperature is set to 120-150° C. and the drying time is 2 hours to ensure that the lignin sulfonate powder has good fluidity.
[0074] Example 6:
[0075] After obtaining the lignin sulfonate solution, polyvinyl alcohol (PVA) or polyacrylic acid (PAA) is added as a modifier at a level of 3-5% of the lignin sulfonate. The solution is heated to 60°C and stirred continuously until the modifier is completely dissolved and evenly distributed. This significantly improves the adhesion and water resistance of the lignin sulfonate, allowing it to maintain good strength even in high-humidity environments. At this point, the lignin sulfonate solution already contains the modifier, and subsequent concentration, drying, and other steps are consistent with the previously described method.
[0076] Comparison of the adhesion and water resistance experimental data of lignin sulfonate with polyvinyl alcohol (PVA) or polyacrylic acid (PAA) modifier and lignin sulfonate without modifier:
[0077] Adhesion test (compressive strength)
[0078] Test method: Use a universal testing machine (test speed of 2 mm / min) to measure the compressive strength of different samples and determine the compressive capacity of the samples under humidity conditions.
[0079]
[0080] Water resistance test (water absorption)
[0081] Test method: The samples were exposed to a high humidity environment (above 80% RH). After 24 hours, the water absorption of the samples was measured to compare the effects of different modifiers on the water resistance of lignin sulfonate.
[0082]
[0083] Compressive strength after hydrolysis
[0084] Test method: The sample was immersed in deionized water for 48 hours, and then its compressive strength was tested and the changes after hydrolysis were analyzed.
[0085]
[0086] Data Analysis and Conclusions:
[0087] Compressive Strength: The addition of polyvinyl alcohol (PVA) or polyacrylic acid (PAA) as modifiers significantly improves the compressive strength of lignin sulfonates. Specifically, under humid conditions, the modified samples exhibited approximately 30-40% higher compressive strength than unmodified samples. Even under high humidity (90% RH), the compressive strength of the PVA- and PAA-modified samples remained close to 7 MPa, significantly better than the 5.6 MPa of unmodified lignin sulfonate.
[0088] Water absorption: The modified lignin sulfonates showed lower water absorption, especially under PVA modification, the water absorption was reduced by 4-5% compared with the unmodified samples, showing the effectiveness of PVA and PAA modifiers in improving the water resistance of lignin sulfonates.
[0089] Strength after hydrolysis: Hydrolysis testing revealed that the modified lignin sulfonate exhibited enhanced resistance to hydrolysis. After immersion, the compressive strength of the PVA-modified sample remained at 5.0 MPa, a 56% increase compared to the unmodified sample (3.2 MPa), demonstrating that the polyvinyl alcohol (PVA) significantly improved the adhesive properties after hydrolysis.
[0090] Example 7:
[0091] Through nitric oxide (NO x ) or ozone treatment of the lignin sulfonate surface to achieve oxidative modification of the lignin sulfonate, further improving its hydrophilicity and activity, thereby enhancing its binding to carbon powder. The oxidation treatment time is controlled to be 30-60 minutes, and the oxidant concentration is 10%.
[0092] Adding nitric oxide (NO x ) or ozone treated lignin sulfonate surface and without adding nitrogen oxide (NO x ) or ozone treatment of lignin sulfonate surface and its hydrophilicity and activity experimental data comparison:
[0093] The following is the experimental data, through the nitrogen oxides (NO x ) or ozone treatment of the lignin sulfonate surface to analyze changes in its hydrophilicity, surface activity, and binding properties with carbon powder. The tests were validated using parameters such as contact angle, surface energy, adsorption rate, and carbon powder binding strength.
[0094] Improved hydrophilicity (contact angle test)
[0095] Test Method: The hydrophilicity of lignin sulfonate surfaces is assessed by measuring the contact angle. The smaller the contact angle, the more hydrophilic the surface. A dynamic contact angle tester was used to measure the contact angles of lignin sulfonate surfaces treated with different methods.
[0096]
[0097] Surface energy test (surface energy calculation)
[0098] Test method: The surface energy of lignin sulfonate under different treatment conditions was measured using the water drop method. A higher surface energy indicates a more active and hydrophilic surface, which is more conducive to bonding with carbon powder.
[0099]
[0100] Carbon powder binding (adsorption rate test)
[0101] Test Method: The binding strength of lignin sulfonate and charcoal powder was measured under different treatment conditions, and the adsorption rate was used to quantify the binding performance. The experiment was conducted by mixing lignin sulfonate and charcoal powder, letting them stand for a certain period of time, and then measuring the change in the mass of the charcoal powder to calculate the adsorption rate.
[0102]
[0103]
[0104] Carbon powder bonding strength test (tensile strength)
[0105] Test Method: A universal tensile testing machine was used to test the bonding strength of lignin sulfonate and carbon powder, measuring the bonding performance under different treatments. The test results are expressed as tensile strength (MPa).
[0106]
[0107] Data Analysis and Conclusions:
[0108] Improvement of hydrophilicity: through nitric oxide (NO x ) and ozone (O3) treatment, the contact angle of the lignin sulfonate surface decreased significantly, from 95.2° without treatment to 72.3° after nitric oxide treatment, and the contact angle after ozone treatment was further reduced to 67.5°, indicating that the surface hydrophilicity was significantly improved.
[0109] Surface energy enhancement: through nitrogen oxides (NO x The surface energy of the lignin sulfonate significantly increased after treatment with nitrogen oxides (NO) and ozone (O3). The surface energy of the untreated sample was 43.6 mN / m, while treatment with NO and ozone increased the surface energy to 55.2 mN / m and 58.3 mN / m, respectively. This indicates that the surface activity has been effectively enhanced, which facilitates the bonding of the lignin sulfonate with the carbon powder.
[0110] Improved carbon powder adsorption: Nitric oxide and ozone treatment significantly increased the adsorption of lignin sulfonate. The adsorption of untreated lignin sulfonate was 38.1%, while the adsorption increased to 49.5% and 52.7% after treatment with nitrogen oxide and ozone, respectively. This indicates that the treated lignin sulfonate has a stronger adsorption capacity and is better able to bind to carbon powder.
[0111] Enhanced bonding strength of carbon powder: Through the tensile strength test, it can be seen that the bonding strength of lignin sulfonate and carbon powder after nitrogen oxide and ozone treatment is significantly improved. The bonding strength of untreated lignin sulfonate and carbon powder is 1.2MPa, and the bonding strength of treated lignin sulfonate and carbon powder is increased to 2.3MPa (NOx treatment) and 2.6MPa (ozone treatment).
[0112] Summary: From the data, we can see that nitrogen oxides (NO x ) and ozone (O3) treatment significantly improved the hydrophilicity and surface activity of lignin sulfonate, enabling it to better bind to carbon powder. Nitric oxide and ozone treatment significantly reduced the contact angle of lignin sulfonate, increased its surface energy, and improved its adsorption rate and carbon powder binding strength. Therefore, nitric oxide and ozone treatment has a significant effect in improving the binding of lignin sulfonate to carbon powder, enhancing the material's performance and showing great potential in carbon adsorbent applications.
[0113] The performance test data of the new carbon adsorbent generated by the above binder are compared as follows: three different binders are used: traditional binder (such as starch), lignin sulfonate and modified lignin sulfonate (with modifiers such as PVA or PAA added);
[0114] Adsorption capacity (unit: mg / g)
[0115] Test the ability of carbon adsorbent in adsorbing certain organic matter or heavy metal ions in water.
[0116]
[0117] Analysis: Modified lignin sulfonates (with PVA or PAA added) exhibited significantly higher adsorption capacity (71.3 mg / g), indicating that the binder possesses improved adsorption properties. The significant improvement in the adsorption capacity of lignin sulfonates by the introduction of modifiers is likely due to increased hydrophilicity and surface activity.
[0118] Mechanical strength (unit: MPa)
[0119] The compressive strength or flexural strength of the carbon adsorbent in a dry state was tested to evaluate its mechanical properties.
[0120]
[0121] Analysis: The modified lignin sulfonate (PVA / PAA) has significantly higher mechanical strength (4.8 MPa), which is significantly higher than that of traditional binders (2.1 MPa) and lignin sulfonate (3.4 MPa). This result shows that the modified lignin sulfonate enhances the hardness and stability of the carbon adsorbent, especially in high-strength applications.
[0122] Water resistance (unit: %)
[0123] The water absorption rate of the carbon adsorbent in a high humidity environment is tested, that is, the changes in the test sample when immersed in water, especially the strength retention rate after wetting.
[0124]
[0125] Analysis: Modified lignin sulfonate (PVA / PAA) exhibits significantly better water resistance in wet environments than traditional binders and standard lignin sulfonate, achieving a wet strength retention rate of 81.2%. Traditional binders exhibit only a wet strength retention rate of 42.3%, indicating significant strength degradation in wet conditions. Lignosulfonate (63.5%) performs better than traditional binders in this regard.
[0126] Thermal stability (unit: ℃)
[0127] Testing the thermal stability of carbon adsorbents to measure whether they can maintain their structure and properties at high temperatures.
[0128]
[0129]
[0130] Analysis: Modified lignin sulfonate (PVA / PAA) has higher thermal stability and can withstand higher temperatures (240°C), which is better than traditional binders (200°C) and lignin sulfonate (220°C). This allows carbon adsorbents with modified lignin sulfonate as a binder to be used at higher temperatures, extending their service life in high-temperature environments.
[0131] This indicates that carbon adsorbents using modified lignin sulfonates as binders exhibit excellent adsorption capacity, mechanical strength, water resistance, and thermal stability, offering superior overall performance compared to traditional binders and standard lignin sulfonates. Modified lignin sulfonates demonstrate significant advantages in improving adsorption capacity and enhancing water resistance, making them suitable for a wider range of applications.
[0132] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like to indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a binder for forming a carbon adsorbent, characterized in that: Includes steps S1: lignin sulfonation reaction: comprising subjecting lignin to a lignin sulfonation reaction with sulfonic acid to obtain lignin sulfonate; S2: Composite modification treatment: lignin sulfonate and natural rubber are mixed in proportion, and the lignin sulfonate and natural rubber are dissolved in deionized water; and the mixture is heated and stirred to form a viscous emulsion; and the water in the solution is removed by a drying method to obtain a composite modified binder powder; S3: Forming of the carbon adsorbent: Mix the composite modified binder and the carbon powder in a mass ratio of 10:90; and extrude and form the mixture through a mold.
2. The method for preparing a binder for forming a carbon adsorbent according to claim 1, characterized in that: The step S1 includes: S11: mixing lignin and sulfonic acid in a mass ratio of 1:4, and adding the mixture into a reactor; S12: heating the reaction vessel to 150-160° C. and stirring the reaction vessel until the sulfonic acid and lignin are fully reacted to produce lignin sulfonate; S13: After the reaction is completed, the mixture is cooled to room temperature, deionized water is added for dilution, and stirred to form a lignin sulfonate solution; S14: removing excess sulfonic acid and concentrating the lignin sulfonate to a solid form.
3. The method for preparing a binder for forming a carbon adsorbent according to claim 1, characterized in that: The step S2 includes: S21: mixing lignin sulfonate and natural rubber in a mass ratio of 9:1; S22: dissolving lignin sulfonate solid and natural rubber in deionized water, the amount of water being 5 times the amount of lignin sulfonate; S23: heating to 60°C and stirring to ensure that the lignin sulfonate and the natural rubber are completely blended; S24: further heating; continuing to heat the solution to 80° C. and stirring until a viscous emulsion is formed; S25: using spray drying or vacuum drying to remove water from the solution to obtain a composite modified binder powder.
4. The method for preparing a binder for forming a carbon adsorbent according to claim 1, characterized in that: The step S1 also includes adding hydrogen chloride gas as a catalyst during the sulfonation reaction to promote the activation of sulfonic acid.
5. The method for preparing a binder for forming a carbon adsorbent according to claim 1, characterized in that: The step S1 of lignin sulfonation reaction also includes using dimethylsulfamide as a solvent to increase the solubility of lignin and the rate of the sulfonation reaction.
6. The method for preparing a binder for forming a carbon adsorbent according to claim 2, characterized in that: In step S13, after obtaining the lignin sulfonate solution, polyvinyl alcohol or polyacrylic acid is added as a modifier and the solution is heated until the modifier is completely dissolved and evenly distributed.
7. The method for preparing a binder for forming a carbon adsorbent according to claim 2, characterized in that: In step S14, after obtaining the lignin sulfonate, the surface of the lignin sulfonate is treated by nitrogen oxide or ozone.